The Application of Social Learning Theory To Understanding Smoking Behavior Among LGBTQ Individuals - Lorenzo Bowman; Larry Bryant (Adult Education Research Conference, 2011)
This study sought to understand the disproportionately higher smoking rates among LGTBQ individuals by employing social learning theory as a tool to analyze the findings from four focus groups conducted among this population in one metro area. The findings indicate that LGBTQ individuals often start smoking after “coming out” in direct response to social stresses and gay culture which seems to be supportive of smoking behavior.
Keywords: LGBTQ Smoking Behavior; Social Learning Theory; sexual orientation; tobacco.